Analisis Faktor- faktor yang Mempengaruhi Kriminalitas Narkoba pada Kalangan Remaja di Jawa Barat - Adiella Farhana HS; Afifah Qolbi Salimah; Dialia Putrina Sepha; Nurli Septiani; Ocha Dahlia Nurcahya; Mic Finanto Ario Bangun (Universitas Palangka Raya, 2024)
The level of aggressiveness and violent crime among teenagers is increasing, with social psychological factors playing an important role in this phenomenon. This research aims to understand the root causes of aggres sive behavior in adolescents and its impact, in order to develop effective intervention strategies. Through literature study methods, this research collects, reads, records and analyzes objectively, systematically, analytically and critically the social and psychological impacts of aggressiveness among adolescents. Results from a review of several journals show that aggressive adolescent behavior is caused by various factors, including hormonal changes, brain development, family parenting, domestic violence, mental disorders, peer influence, and media exposure.